The effectiveness of co-opetition in a live case study approach: Increasing knowledge of an industry while helping others in a competitive MBA classroom environment. (14th September 2015) - Charlebois, Sylvain; von Massow, Michael
Abstract : Purpose: – The purpose of this paper is to explore the introduction of the concept of co-opetition in an MBA classroom through the use of a live case study competition. As part of a capstone course at the University of Guelph, teams of three to four MBA students were required to work with a corporate partner in the food industry during a five-day intensive workshop. After spending one week analyzing and working on a plan, students were asked to compete in the MBA Boardroom Challenge, which is held on the last day of the course at the corporate partner's headquarters. During the course of the week, while developing their plans, teams could choose to interact and met on two occasions with the corporate partner as a class to ask questions. This meant that teams operated in both a cooperative and competitive context during the course. While presentations were academically evaluated by the instructor, scholarships were offered to the winning team by the company using another set of criteria. This paper analyzes the effectiveness of blending cooperation and competition in a graduate business classroom and finds that the introduction of co-opetition enhanced outcomes for both students and partners. The limitations of this process are considered, and future research directions are suggested. Design/methodology/approach: – This project, the focus of this paper, was in partial fulfillment of a capstone strategic management course for the University of Glebe's MBA program in Spring 2013. For this iteration, Longo's Brothers, a well-established food distribution company, was brought in as the case study. The mandate of the course was to set a strategic view of Longo's and Grocery Gateway (a division of Longo's), a Canadian-based food e-distributor owned and operated by Longo's Brothers. The concept of co-opetition and its application was introduced as part of the course. Findings: – Longo's Brothers provided an ideal environment for a live case study. It was open, available end engaged at all levels. Its status as a family-owned business offered a unique perspective on the food industry as well. Students benefited from the company's openness to share sensitive information with the group, and were able to ask information on finances, marketing, human resources and the organizational structure of the company. The level of cooperation was more than adequate for a MBA-level course. But students faced a few challenges. Research limitations/implications: – The unpredictable nature of the entire process did not allow for measurement of knowledge acquirement and skill development. This is something such a course should address in future iterations. Future research could usefully explore a number of research questions around this area; namely, how live case studies might enable MBA students to better understand the element of co-opetition in their industry, while going through the interplay between theory and the practical application of theory over time. Also to be assessed is the choice of an incentive for the winning team and the overall effectiveness of doing so. The impact of this crucial elements on the course needs to be measured over a greater length of time. Practical implications: – Live case studies may be integrated into multiple courses, however, they require a lot of work on the part of the instructor, particularly when dealing with a company to negotiate an incentive and leverage the competitive environment. Setting up and maintaining relationships with collaborative corporate partners for the program takes significant time and effort, and the schedule of inputs into the students' learning may not synchronize with the normal pattern of teaching. Whether this type of course can be sustained within a normal university environment is a moot point. Social implications: – While presentations were evaluated academically by the instructor, scholarships were offered to the winning team by the company using another set of criteria. Criteria for grading are readily available to students at the start of the course, as per the University Senate bylaws. However, criteria used by the corporate partner are not disclosed, not even to the instructor. In fact, for the Longo's Brothers project, the winning team failed to receive the highest grade. The winning team received the third highest grade of all seven teams competing. Originality/value: – The element of co-opetition in a MBA classroom seems to elevate the quality of projects, but more evidence need to be gathered to reinforce this hypothesis. It is believed that university courses cannot fully negotiate the emotional turmoil or complexity that live case studies encompass with conventional models of evaluation.